Feedback active noise control system and its application to MRI noise - Kajikawa, Y. (2011 8th International Conference on Information, Communications and Signal Processing, 2011)
In this paper, a novel feedback active noise control (ANC) system combining a linear prediction filter and its application to reducing noise generated from magnetic resonance imaging (MRI) devices (MRI noise) are introduced. The proposed ANC system can reduce narrowband noise while suppressing a disturbance with broadband components. Such a disturbance makes a conventional feedback ANC system unstable or divergent because the disturbance corrupts the input signal to the system. In the proposed ANC system, a linear prediction filter is combined with the feedback ANC system to suppress the disturbance. Moreover, a modified-error feedback ANC system that can update the noise control filter using an ordinary adaptive algorithm such as NLMS instead of the Filtered-x algorithm is also incorporated with the linear prediction filter. In the modified-error feedback ANC system, not only the stability but also the convergence rate and noise reduction ability can be improved. Simulation results demonstrate that the proposed feedback ANC systems are superior to conventional feedback ANC systems in terms of the stability, convergence rate, and noise reduction ability. Furthermore, the proposed ANC system is applied to reducing MRI noise. MRI noise consists of many sinusoidal waves whose amplitude varies with time. We found that the feedback ANC system can effectively reduce MRI noise. The proposed ANC system is implemented in a head-mounted structure to control the noise near the user's ears and to compensate for the low output of compact loudspeakers. Experimental results demonstrate that the proposed ANC system with head-mounted structure can significantly reduce MRI noise by approximately 30 dB in a high field in an actual MRI room even if the imaging mode changes frequently.